Respostas

A melhor resposta!
2014-06-25T19:29:48-03:00
f(x)=3x-2\\ g(x)=2x+1\\ \\ f(g(2))=2(2)+1\\ f(g(2))=4+1\\ f(g(2))=5\\ f(5)=3(5)-2\\ f(5)=15-2\\ f(5)=13\\ \\ g(f(-1))=3(-1)-2\\ g(f(-1))=-3-2\\ g(f(-1))=-5\\ g(-5)=2(-5)+1\\ g(-5)=-10+1\\ g(-5)=-9
2 5 2
Muito Obrigado!!!
Por nada querida. :D
2014-06-25T19:44:28-03:00
Isto é uma função composta, sua resolução se dá da seguinte forma

f(g(x)) = 3(2x - 1) - 2 ⇒ f(g(x)) = 6x - 3 -2 ⇒ f(g(x)) = 6x - 5 ⇒ f(g(-2)) = - 12 - 5  = - 17

f(g(2)) = 12 - 5 = 7

g(f(x)) = 2(3x - 2) + 1 ⇒ g(f(x)) = 6x - 4 +1 ⇒ g(f(x)) = 6x - 3 ⇒ g(f(- 1)) = - 6 - 3 = - 9